Intel Technology, Inc : The Winning Strategies - Lim, Grace Yee Chuen (2004)
The objective of this thesis is to enable Intel Corporate to remain competitive as the global technology leader and enable Intel Malaysia to be one of the prime offshore sites for Intel Corporate.